A Dynamic Extension of the Foster-Hart Measure of Riskiness - Tobias Hellmann; Frank Riedel (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
We analyze the Foster-Hart measure of riskiness for general distributions in dynamic settings. The Foster-Hart measure avoids bankruptcy in the long run. It is not time-consistent.
urn:nbn:de:0070-pub-26999870
Keywords: D81; G11; 330; Dynamic Risk Measures; Time-Consistency; Bankruptcy; Continuous Random Variable